A unique low light adaptation mechanism in Rhodobacter azotoformans. (11th September 2014) - Li, Kai; Zhao, Chungui; Yue, Huiying; Yang, Suping
<x xml:space="preserve">Abstract</x> In this paper, we reported for the first time that Rhodobacter azotoformans was capable of synthesizing a spectral variant of peripheral light‐harvesting complex (LH3), besides a high light form (LH2), in response to low light intensity. Carotenoid components in these complexes were analyzed by absorption spectra, high‐pressure liquid chromatography and mass spectroscopy analysis. Only spheroidene carotenoid was detected in LH2, while LH3 possessed three kinds of carotenoids, spheroidene, spirilloxanthin, and anhydrorhodovibrin. The spirilloxanthin and anhydrorhodovibrin predominated in LH3 and were rarely found in Rhodobacter species. Carotenoid‐to‐bacteriochlorophyll energy transfer efficiency in LH3 increased by 4% compared to that in LH2. Raman spectroscopic properties of carotenoids in both complexes supported the view that carotenoids altered their planar configuration to a distorted form by interaction with protein matrix in response to low light conditions. In conclusion, the low light adaptation mechanism of Rba. azotoformans involved regulating the synthesis of LH3 and additional carotenoids as well as the configuration change of incorporated carotenoids.